Effect Of Surface Geometry And Pretension Level On Vibration Of Tensioned Membrane Structures - Low, Yan May (Universiti Sains Malaysia, 2021)
This thesis was carried out to investigate the impacts of different surface geometry and varying application of pre-tension level respectively on the vibration of membrane structures. In this paper, a total of 60 models generated from anticlastic membrane structures such as cone shaped and simple hyperbolic paraboloid (simple hypar) structures were analysed. A finite element software known as SOFiSTiK was adopted for the modelling process and dynamic analysis of the designed membrane structures. There were two vital analysis which had been performed in this study: form-finding analysis and free vibration analysis. The former represents the process of a membrane structure which tends to achieve its equilibrium shape under the prescribed pretension level and surface geometry while the latter implies the development of natural frequency due to initial self-vibration retained by the membrane structure itself without the disturbance of external loads. Based on this analysis, a series of graphs on overall frequency and lowest frequency for each type of models were plotted. In this case, two types of frequency graphs were presented at which the first graph was used to show the relationship between natural frequency and different surface geometry whilst second graph was produced to demonstrate the link amidst natural frequency and pretension level applied on the membrane structures. It had been founded that most of the membrane structures exhibit a nonlinearly increase in frequency under the variation of surface geometry and pretension level. Therefore, a conclusion was made where the effect of surface geometry and pretension level on membrane structures was significant towards the fundamental vibration of the structures. The outcome of this study can be used as reference for structural designers for the evaluation of dynamic characteristics of membrane structures under effect of wind loading.